Fatal deep venous thrombosis and pulmonary embolism secondary to melioidosis in China: case report and literature review - Wu, Hua; Huang, Dongliang; Wu, Biao; Pan, Mengjie; Lu, Binghuai (BMC infectious diseases, 2019)
Burkholderia pseudomallei is a gram-negative bacterium and the causative pathogen of melioidosis, which manifests a variety ranges of infection symptoms. However, deep venous thrombosis (DVT) and pulmonary embolism (PE) secondary to bacteremic melioidosis are rarely documented in the literature. Herein, we reported a fatal case of melioidosis combined with DVT and PE. A 54-year-old male construction worker and farmer with a history of diabetes was febrile, painful in left thigh, swelling in left lower limb, with chest tightness and shortness of breath for 4 days. He was later diagnosed as DVT of left lower extremity and PE. The culture of his blood, sputum and bone marrow samples grew B. pseudomallei. The subject was administrated with antibiotics (levofloxacin, cefoperazone/tazobactam, and imipenem) according to antimicrobial susceptibility testing and low molecular heparin for venous thrombosis. However, even after appropriate treatment, the patient deteriorated rapidly, and died 2 weeks after admission. This study enhanced awareness of the risk of B. pseudomallei bloodstream infection in those with diabetes. If a patient has predisposing factors of melioidosis, when DVT is suspected, active investigation and multiple therapeutic interventions should be implemented immediately to reduce mortality rate.